Problems and Prospects for the Development of Doctoral Education in Russia: The View of Regional Universities - E. A. Terentev; B. I. Bednyi (Moscow Polytechnic University, 2020)
The concentration of state resources in the leading universities poses the problem of reproduction of the scientific and pedagogical personnel in regional universities that do not participate in state-funded academic excellence programs. Based on the data from three focus group interviews with heads of doctoral studies offices at regional universities, the article analyzes problems arising in the implementation of the current model of training and certification of doctoral students. Four following groups of problems are identified: 1) the rigidity of requirements for the structure and content of the educational programs, 2) the imperfection of the system of attestation, gaps between attestation activities, 3) the problem of "retention" of doctoral students after the completion of the educational program, 4) the problems of conjugation of the processes of preparing a dissertation and its defense. The authors discuss possible ways to overcome the identified problems through providing universities with greater autonomy in designing the structure and content of the educational programs; synchronization of the procedures of the final state attestation and dissertation defense; creation of mechanisms for supporting successful doctoral graduates at the final stage of their preparation for the defense of a dissertation; development of network forms for implementation of doctoral programs with leading universities and research institutes.